B-cell development and antigen receptor signalling. (August 2002) - Turner, M.
Abstract : B-cell development and function requires the products of the Vav family of genes. Vav proteins act as key components of the antigen receptor signal transduction machinery by integration of signals that control the cell cycle, differentiation and apoptosis. At the molecular level, Vav proteins regulate small-molecular-mass GTPases, phosphoinositide 3-kinase, TEC family tyrosine kinases and intracellular calcium flux.